2016
DOI: 10.1007/s10620-015-4013-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Health-Related Quality of Life in Patients with Primary Sclerosing Cholangitis

Abstract: Patients with PSC have significantly lower HRQoL than healthy controls. Both symptoms of IBD and chronic liver disease impact HRQoL in patients with PSC, which lead to significant psychologic burden that is expressed by existential anxieties and social isolation. A PSC-specific HRQoL tool is critical to adequately quantify the distinct impact of IBD and cholestatic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 25 publications
6
76
3
1
Order By: Relevance
“…Few reports have already indicated the negative impact of PSC on HRQoL [3,4]. In our previous study, we observed an impairment in quality of life for patients with PSC compared to healthy individuals, and our data highlighted a significant impact of female gender in predicting worse quality of life [2].…”
Section: Discussionsupporting
confidence: 61%
“…Few reports have already indicated the negative impact of PSC on HRQoL [3,4]. In our previous study, we observed an impairment in quality of life for patients with PSC compared to healthy individuals, and our data highlighted a significant impact of female gender in predicting worse quality of life [2].…”
Section: Discussionsupporting
confidence: 61%
“…This is in stark contrast to, for example, chronic autoimmune cholestatic diseases which may affect a comparable number of adults. Indeed, HRQoL has been thoroughly investigated in primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) showing that both conditions significantly affect patient well‐being . Everyday clinical experience clearly demonstrates that individuals with AIH also struggle with serious symptoms significantly affecting their well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…Pruritus with chronic liver disease is a refractory symptom and it reduces the patients’ quality of life (QOL) . However, without enough investigation by physicians and medical personnel, the symptom of pruritus could be missed.…”
Section: Introductionmentioning
confidence: 99%